Acid and alkali resistant UV viscosity-reducing adhesive tape as well as preparation method and application thereof
By using an adhesive layer composed of polyurethane acrylate polymer and PO film layer, the problem of poor acid and alkali resistance in an acid-base environment is solved, and high initial peeling force and good protection effect is achieved.
Patent Information
- Application Number
- CN202510369320.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing UV adhesive tape has poor acid and alkali resistance in acid-base environments, which can easily cause damage to the subject to be applied due to acid and alkali.
An adhesive layer consisting of a polyurethane acrylate polymer, a photoinitiator and a curing agent is used to form an acid-base-resistant UV adhesive tape with a tensile strength of 15 to 30 MPa.
Maintain good physical and chemical properties in an acid-base environment, has high initial peeling force, and the peeling force drops rapidly after UV energy illumination, is easy to remove, and can effectively protect the sticking object.
Smart Images

Figure CN119875529A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, and in particular to an acid-base resistant UV adhesive tape and a preparation method and application thereof. Background Art
[0002] The anti-viscosity adhesive is a protective film made of polymer materials. The product has a high adhesion before the anti-viscosity, and the adhesive itself is quickly lost through the use of light, heat, electricity and other treatments. During the processing, the product realizes the functions of effective fixation and transfer of the object being pasted.
[0003] At present, the process of reducing viscosity is mainly achieved by UV reducing viscosity. However, since many components need to be acid-washed or alkaline-washed during processing, such as thinning of glass, semiconductor and other structures, the reducing viscosity composition in ordinary UV reducing viscosity tape is made of acrylic acid polymerized, and the ester bond in acrylic acid is prone to hydrolysis. Especially in high temperature or strong acid and alkali environment, the hydrolysis speed is accelerated, and acrylic acid and corresponding alcohol will be formed after the ester bond is broken. The molecular chain of acrylic acid is short and the chemical stability is low, which leads to the decline or decomposition of material performance. The existing UV reducing viscosity tape cannot withstand the corrosion of acid and alkali, and has poor acid and alkali resistance, which easily causes the object to be attached to be damaged by acid and alkali. Summary of the invention
[0004] In response to the problems raised by the background technology, the purpose of the present invention is to propose an acid and alkali resistant UV anti-adhesive tape, which has good acid and alkali resistance, high initial peeling force, and rapid decrease in peeling force after UV energy exposure. It is easy to remove, has little change in peeling force under acid and alkali scenarios, and has no residual glue after peeling. It can provide good protection for the adhered object in acid and alkali scenarios, solving the technical problems that the existing UV anti-adhesive tape has poor acid and alkali resistance and easily causes the adhered object to be damaged by acid and alkali.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned acid and alkali resistant UV anti-viscosity tape.
[0006] Another object of the present invention is to propose the application of the above-mentioned acid and alkali resistant UV anti-adhesive tape in the fields of wafer cutting, semiconductors, glass thinning and 3C electronic materials.
[0007] The above technical objectives of the present invention are achieved through the following technical solutions: An acid-base resistant UV anti-adhesive tape, comprising a PO film layer, an adhesive layer and a release film layer arranged in sequence from top to bottom; Calculated by weight, the raw materials of the adhesive layer include the following components: 100 parts of polyurethane acrylate polymer, 0.1 to 1 parts of photoinitiator and 0.2 to 2 parts of curing agent; The raw materials of the polyurethane acrylate polymer include the following components calculated by weight: 5 to 40 parts of butyl acrylate, 10 to 45 parts of hydroxyethyl acrylate, 2 to 20 parts of isocyanate, 1 to 10 parts of multifunctional acrylate, 0.1 to 5 parts of initiator and 100 parts of solvent; The multifunctional acrylate is selected from any one or more combinations of trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate; The material of the PO film layer is a PO film, the tensile strength of the PO film is 15-30 MPa, and the elongation at break is 400%-800%; The thickness of the adhesive layer is 5 to 200 μm; The molecular weight of the polyurethane acrylate polymer is 300,000 to 1,000,000 Daltons, and the solid content is 30 to 50%.
[0008] To further illustrate, the isocyanate is selected from any one or more combinations of 4-phenylbenzyl isocyanate, isophorone diisocyanate, 3-ethylphenyl isocyanate, octadecyl isocyanate, p-toluene isocyanate and triphenylmethane triisocyanate.
[0009] To further illustrate, in the raw materials of the polyurethane acrylate polymer, the initiator is selected from any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, benzoyl peroxide, tert-butyl peroxyhexahydroterephthalate and tert-butyl peroxy-2-ethylhexyl ester.
[0010] To further illustrate, the solvent is selected from any one or more combinations of toluene, ethyl acetate, butyl acetate and butanone.
[0011] Further, in the raw materials of the bonding layer, the photoinitiator is selected from any one or more combinations of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone and 2,4,6-(trimethylbenzoyl)-diphenylphosphine oxide.
[0012] Further, the curing agent is selected from any one or more combinations of Bayer L75 curing agent, Bayer N3300 curing agent, Bayer 3175 curing agent and Covestro N75 curing agent.
[0013] A method for preparing an acid- and alkali-resistant UV adhesive tape, which is used to prepare the acid- and alkali-resistant UV adhesive tape, comprises the following steps: Step S1, preparing polyurethane acrylate polymer: Step S11, stirring and refluxing the formulated amounts of butyl acrylate, hydroxyethyl acrylate, isocyanate, initiator and solvent at a temperature of 35-45° C.; Step S12, stirring and reacting until the viscosity reaches 200-300 mPa·s, slowly adding multifunctional acrylate at a dropping rate of 0.01 g / min-0.1 g / min, and cooling after the multifunctional acrylate is added and the reaction is completed, to obtain a polyurethane acrylate polymer; Step S2: Preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, baking at a temperature of 60-100° C. for 5-10 minutes to obtain the adhesive layer, covering it with a release film, and obtaining an acid-base resistant UV anti-viscosity tape.
[0014] The acid-base resistant UV anti-adhesive tape is used in the fields of wafer cutting, semiconductors, glass thinning and 3C electronic materials.
[0015] Compared with the prior art, the embodiments of the present invention have the following beneficial effects: The polyurethane acrylate polymer in the above-mentioned acid- and alkali-resistant UV anti-viscosity tape can maintain good physical and chemical properties in an acid- and alkali-resistant environment due to the combined effects of its stable molecular structure, cross-linking density and hydrophobic groups, and has good acid- and alkali-resistant effects. At the same time, a PO film with a tensile strength of 15 to 30 MPa and an elongation at break of 400% to 800% is used. The PO film has good mechanical properties and can be well attached to the adhered object without warping around, further preventing acid and alkali liquids from penetrating the sides to damage the adhered object. The acid- and alkali-resistant UV anti-viscosity tape made using a PO film of this strength as a substrate and polyurethane acrylate has a high initial peel force, and the peel force before UV energy irradiation is above 1800gf / 25mm. The bonding strength is large and has been exposed to 400 to 10000mj / cm 2 After being exposed to UV energy, the peeling force drops rapidly, the adhesive is lost instantly, and it is easy to remove. The peeling force changes little in acid and alkali scenarios, and there is no residual adhesive after peeling. It can provide good protection for the adhered object in acid and alkali scenarios, solving the technical problems of poor acid and alkali resistance of existing UV anti-adhesive tapes and easy damage to the adhered objects due to acid and alkali. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic structural diagram of an acid and alkali resistant UV viscosity reducing tape according to an embodiment of the present invention.
[0017] Among them: PO film layer 1, adhesive layer 2, release film layer 3. DETAILED DESCRIPTION
[0018] An acid-base resistant UV anti-adhesive tape comprises a PO film layer 1, an adhesive layer 2 and a release film layer 3 arranged in sequence from top to bottom; Calculated by weight, the raw materials of the adhesive layer 2 include the following components: 100 parts of polyurethane acrylate polymer, 0.1-1 parts of photoinitiator and 0.2-2 parts of curing agent; The raw materials of the polyurethane acrylate polymer include the following components calculated by weight: 5 to 40 parts of butyl acrylate, 10 to 45 parts of hydroxyethyl acrylate, 2 to 20 parts of isocyanate, 1 to 10 parts of multifunctional acrylate, 0.1 to 5 parts of initiator and 100 parts of solvent; The multifunctional acrylate is selected from any one or more combinations of trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate; The material of the PO film layer 1 is a PO film, and the tensile strength of the PO film is 15-30 MPa, and the elongation at break is 400%-800%.
[0019] The raw material of the adhesive layer 2 of the present invention is polyurethane acrylate polymer, and the polyurethane acrylate polymer is synthesized from butyl acrylate, hydroxyethyl acrylate, isocyanate, multifunctional acrylate, initiator and solvent. In the process of synthesizing the polyurethane acrylate polymer, hydroxyethyl acrylate reacts with isocyanate to obtain acrylic modified polyurethane (PU), and the reaction process is as follows: ; In addition, the double bonds of the acrylate raw materials in the raw materials will crack during the polymerization process and copolymerize with other acrylate monomers to form a cross-linked structure (wherein the acrylate raw materials and acrylate monomers include butyl acrylate and multifunctional acrylate, respectively), and the acrylate raw materials also react with acrylic modified polyurethane (PU) to form a cross-linked structure with polyurethane groups. The chemical bond stability of the synthesized polyurethane acrylate polymer is high. The chemical bonds (such as carbon-nitrogen bonds and carbon-oxygen bonds) in acrylic modified polyurethane (PU) have relatively high stability under acidic conditions and are not easily destroyed by acid. These bonds can resist acid erosion and maintain the physical strength and integrity of the material. The denser the cross-linked structure formed, the higher the stability of the material. The cross-linked network can limit the diffusion of acidic substances and reduce the permeability and destructive power of acid on the material.
[0020] In addition, the molecular chain of polyurethane acrylate polymer contains strongly covalently bonded carbamate bonds and acrylate segments. The carbamate group (-NHCOO-) has high chemical stability and can maintain its structure in an acidic and alkaline environment. This makes the molecular chain of the material relatively fixed and not easily corroded by acid and alkali. The cross-linked network structure can improve the chemical corrosion resistance of the material. At the same time, the (-NHCOO-) in the structure of polyurethane acrylate can maintain its structure in an acidic and alkaline environment and is difficult to be eroded by protons (H + ) attack, so it is not easy to depolymerize or decompose in an acidic environment. This stability enhances the resistance of the polyurethane part to acid. The side groups in multifunctional acrylates, such as hydroxyl groups (-OH), can react with protons (H + ) neutralizes the acid and temporarily reduces the acid's erosion on the polymer chain. This local acid neutralization can slow down the acid's damage to a certain extent. Hydrophobic groups such as methyl CH3-, ethyl CH3CH2- and butyl CH3(CH2)3- can effectively resist the erosion of water-soluble acids and bases, reduce the damage of acids and bases to the internal structure of the polymer, and their low polarity makes them inert in chemical reactions, reducing the impact of acids and bases on the surface of the material.
[0021] In addition, among the raw materials of the adhesive layer 2, the added amount of the photoinitiator is 0.1 to 1 parts. If the added amount of the photoinitiator is too little, it will lead to poor viscosity reduction effect after UV energy irradiation; the added amount of the curing agent is 0.2 to 2 parts. If the added amount of the curing agent is too much, it will lead to poor wettability of the adhesive layer 2, resulting in low initial bonding strength. If the added amount of the curing agent is too little, it will lead to poor cohesion of the colloid and easy residual glue.
[0022] In summary, the acid and alkali resistance of polyurethane acrylate is the result of the combined effect of its stable molecular structure, cross-linking density and hydrophobic groups, which enables polyurethane acrylate polymers to maintain good physical and chemical properties in acid and alkali environments, and has good acid and alkali resistance. At the same time, a PO film with a tensile strength of 15-30MPa and an elongation at break of 400%-800% is used. The PO film has good mechanical properties and can be well attached to the object being adhered without warping around the edges, further preventing acid and alkali liquids from penetrating the sides to damage the object being adhered. The acid and alkali resistant UV adhesive tape made using a PO film of this strength as a substrate and polyurethane acrylate has a high initial peel force, and the peel force before UV energy irradiation is above 1800gf / 25mm. The bonding strength is high and after 400-10000mj / cm 2After being exposed to UV energy, the peeling force drops rapidly, the adhesive is lost instantly, and it is easy to remove. The peeling force changes little in acid and alkali scenarios, and there is no residual adhesive after peeling. It can provide good protection for the adhered object in acid and alkali scenarios, solving the technical problems of poor acid and alkali resistance of existing UV anti-adhesive tapes and easy damage to the adhered objects due to acid and alkali.
[0023] To further illustrate, the thickness of the adhesive layer 2 is 5 to 200 μm.
[0024] The adhesive layer 2 of a certain thickness is formed by coating. If the thickness of the adhesive layer 2 is too small, it is easy to cause insufficient bonding force. If the thickness of the adhesive layer 2 is too large, the process control of the coating process is troublesome and the colloid will have bubbles. Therefore, the thickness of the adhesive layer 2 is 5 to 200 μm, which can not only ensure the bonding force, but also meet the coating process requirements and the terminal use requirements of the product.
[0025] It is further described that the molecular weight of the polyurethane acrylate polymer is 300,000 to 1,000,000 Daltons, and the solid content is 30 to 50%.
[0026] The solid content is high and the molecular weight is also high. The molecular weight of the prepared polyurethane acrylate polymer is in the range of 300,000 to 1 million Daltons, and the solid content is in the range of 30 to 50%, which can ensure that the colloid has a high initial adhesion and can quickly lose viscosity after UV.
[0027] To further illustrate, the isocyanate is selected from any one or more combinations of 4-phenylbenzyl isocyanate, isophorone diisocyanate, 3-ethylphenyl isocyanate, octadecyl isocyanate, p-toluene isocyanate and triphenylmethane triisocyanate.
[0028] To further illustrate, in the raw materials of the polyurethane acrylate polymer, the initiator is selected from any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, benzoyl peroxide, tert-butyl peroxyhexahydroterephthalate and tert-butyl peroxy-2-ethylhexyl ester.
[0029] To further illustrate, the solvent is selected from any one or more combinations of toluene, ethyl acetate, butyl acetate and butanone.
[0030] To further illustrate, among the raw materials of the bonding layer 2, the photoinitiator is selected from any one or more combinations of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone and 2,4,6-(trimethylbenzoyl)-diphenylphosphine oxide.
[0031] Further, the curing agent is selected from any one or more combinations of Bayer L75 curing agent, Bayer N3300 curing agent, Bayer 3175 curing agent and Covestro N75 curing agent.
[0032] A method for preparing an acid- and alkali-resistant UV adhesive tape, which is used to prepare the acid- and alkali-resistant UV adhesive tape, comprises the following steps: Step S1, preparing polyurethane acrylate polymer: Step S11, stirring and refluxing the formulated amounts of butyl acrylate, hydroxyethyl acrylate, isocyanate, initiator and solvent at a temperature of 35-45° C.; Step S12, stirring and reacting until the viscosity reaches 200-300 mPa·s, slowly adding multifunctional acrylate at a dropping rate of 0.01 g / min-0.1 g / min, and cooling after the multifunctional acrylate is added and the reaction is completed, to obtain a polyurethane acrylate polymer; Step S2: Preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer 2; Step S22, coating the raw material of the adhesive layer 2 on the PO film, baking at a temperature of 60-100° C. for 5-10 minutes to obtain the adhesive layer 2, and covering it with a release film to obtain an acid-base resistant UV anti-viscosity tape.
[0033] The preparation method of the acid-base resistant UV anti-viscosity tape of the present invention comprises the following steps: firstly stirring and refluxing butyl acrylate, hydroxyethyl acrylate, isocyanate, initiator and solvent, and then dripping multifunctional acrylate after a certain polymerization of hydroxyethyl acrylate and isocyanate, so as to avoid gelation and implosion caused by premature addition of multifunctional acrylate, and then dripping multifunctional acrylate when the viscosity is 200-300mPa·s. If the multifunctional acrylate is added too late, it is not easy to participate in polymerization. Since multifunctional acrylate is easy to crosslink, it is necessary to control its crosslinking reaction to prevent gelation, so it is necessary to control the dripping rate to 0.01g / min-0.1g / min. After obtaining the polyurethane acrylate polymer, the polyurethane acrylate polymer, the photoinitiator and the curing agent are evenly mixed, and coated on the PO film, and the release film is covered to obtain the acid-base resistant UV anti-viscosity tape. The obtained polyurethane acrylate polymer can maintain good physical and chemical properties in an acid-base environment, and has good acid-base resistance effect. At the same time, the PO film with a tensile strength of 15-30MPa and a breaking elongation of 400%-800% can be well attached to the object being attached without warping around the edges, further preventing acid and alkali liquids from penetrating the sides and damaging the object being attached. The acid and alkali resistant UV adhesive tape made using the PO film of this strength as the substrate has a high initial peeling force, and the peeling force before UV energy irradiation is above 1800gf / 25mm, with high bonding strength, and after 400-10000mj / cm 2 After being exposed to UV energy, the peeling force drops rapidly, the adhesive is lost instantly, and it is easy to remove. The peeling force changes little in acid and alkali scenarios, and there is no residual adhesive after peeling. It can provide good protection for the adhered object in acid and alkali scenarios, solving the technical problems of poor acid and alkali resistance of existing UV anti-adhesive tapes and easy damage to the adhered objects due to acid and alkali.
[0034] Further explanation, in step S12, the dripping rate of the multifunctional acrylate is 0.01 g / min to 0.1 g / min, and the dripping rate can prevent gelation and ensure that the multifunctional acrylate participates in polymerization. In addition, when the multifunctional acrylate is slowly dripped, it is dripped until the viscosity is 600 to 1200 mPa·s, and the multifunctional acrylate is dripped and the reaction is completed. Since the addition of the multifunctional acrylate will produce cross-linking, it is necessary to control the viscosity range of the polyurethane acrylate polymer to facilitate the construction of the raw materials of the subsequent adhesive layer 2. If the viscosity is too low, it is easy to flow and difficult to form a film. If the viscosity is too high, it is easy to explode and gel.
[0035] Specifically, the baking is performed at a temperature of 60 to 100° C. for 5 to 10 minutes so that the solvent can be completely volatilized.
[0036] Specifically, the material of the release film layer 3 is a release film.
[0037] The acid-base resistant UV anti-adhesive tape is used in the fields of wafer cutting, semiconductors, glass thinning and 3C electronic materials.
[0038] The acid-base resistant UV anti-adhesive tape can be used as a surface protection film and a masking tape product for coating in the fields of wafer cutting, semiconductors, glass thinning and 3C electronic materials, and is particularly suitable for use in the fixing and cutting processes of various electronic components in acid-base scenarios.
[0039] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0040] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] According to the following preparation method, step S1 is carried out to prepare a polyurethane acrylate polymer, and polyurethane acrylate polymer A, polyurethane acrylate polymer B, polyurethane acrylate polymer C, polyurethane acrylate polymer D, polyurethane acrylate polymer E, polyurethane acrylate polymer F and polyurethane acrylate polymer G are prepared respectively, and the raw materials are calculated by weight.
[0042] The preparation of polyurethane acrylate polymer A comprises the following steps: Step S11, adding 8 parts of butyl acrylate, 10 parts of hydroxyethyl acrylate, 3 parts of isocyanate (4-phenylbenzyl isocyanate), 0.2 parts of initiator (azobisisobutyronitrile), and 100 parts of solvent (toluene) into a reaction kettle, and stirring and refluxing at a temperature of 40° C.; Step S12, stirring the reaction until the viscosity reaches 300 mPa·s, slowly adding 8 parts of multifunctional acrylate (trimethylolpropane trimethacrylate), controlling the dropping rate to 0.08 g / min, and adding until the viscosity reaches 1200 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining polyurethane acrylate polymer A, the molecular weight of polyurethane acrylate polymer A is 1 million Daltons, and the solid content is 50%.
[0043] The preparation of polyurethane acrylate polymer B comprises the following steps: Step S11, adding 12 parts of butyl acrylate, 15 parts of hydroxyethyl acrylate, 5 parts of isocyanate (isophorone diisocyanate), 0.5 parts of initiator (azobisisoheptanenitrile), and 100 parts of solvent (ethyl acetate) into a reaction kettle, and stirring and refluxing at a temperature of 38° C.; Step S12, stirring the reaction until the viscosity reaches 280 mPa·s, slowly adding 6 parts of multifunctional acrylate (trimethylolpropane triacrylate), controlling the dropping rate to 0.07 g / min, and adding until the viscosity reaches 1000 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining polyurethane acrylate polymer B, the molecular weight of polyurethane acrylate polymer B is 950,000 Daltons, and the solid content is 48%.
[0044] The preparation of polyurethane acrylate polymer C comprises the following steps: Step S11, add 20 parts of butyl acrylate, 22 parts of hydroxyethyl acrylate, 8 parts of isocyanate (3-ethylphenyl isocyanate), 0.7 parts of initiator (azobisisovaleronitrile), and 100 parts of solvent (a mixed solvent of 80 parts of ethyl acetate and 20 parts of butanone) into a reaction kettle, and stir and reflux at a temperature of 35° C.; Step S12, stirring the reaction until the viscosity reaches 250 mPa·s, slowly adding 4 parts of multifunctional acrylate (trimethylolpropane triacrylate), controlling the dropping rate to 0.05 g / min, and adding until the viscosity reaches 800 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining polyurethane acrylate polymer C, the molecular weight of polyurethane acrylate polymer C is 880,000 Daltons, and the solid content is 45%.
[0045] The preparation of polyurethane acrylate polymer D comprises the following steps: Step S11, add 25 parts of butyl acrylate, 20 parts of hydroxyethyl acrylate, 12 parts of isocyanate (octadecyl isocyanate), 1 part of initiator (tert-butyl peroxyhexahydroterephthalate), and 100 parts of solvent (a mixed solvent of 80 parts of ethyl acetate and 20 parts of toluene) into a reaction kettle, and stir and reflux at a temperature of 35° C.; Step S12, stirring the reaction until the viscosity reaches 230 mPa·s, slowly adding 2 parts of multifunctional acrylate (pentaerythritol triacrylate), controlling the dropping rate to 0.08 g / min, and adding until the viscosity reaches 600 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining a polyurethane acrylate polymer D, the molecular weight of the polyurethane acrylate polymer D is 820,000 Daltons, and the solid content is 43%.
[0046] The preparation of polyurethane acrylate polymer E comprises the following steps: Step S11, add 5 parts of butyl acrylate, 10 parts of hydroxyethyl acrylate, 2 parts of isocyanate (isophorone diisocyanate), 0.1 parts of initiator (azobisisoheptanenitrile), and 100 parts of solvent (ethyl acetate) into a reaction kettle, and stir and reflux at a temperature of 38° C.; Step S12, stirring the reaction until the viscosity reaches 280 mPa·s, slowly adding 1 portion of multifunctional acrylate (trimethylolpropane triacrylate), controlling the dropping rate to 0.07 g / min, and adding until the viscosity reaches 600 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining a polyurethane acrylate polymer E, the molecular weight of the polyurethane acrylate polymer E is 800,000 Daltons, and the solid content is 42%.
[0047] The preparation of polyurethane acrylate polymer F comprises the following steps: Step S11, adding 40 parts of butyl acrylate, 45 parts of hydroxyethyl acrylate, 20 parts of isocyanate (isophorone diisocyanate), 5 parts of initiator (azobisisoheptanenitrile), and 100 parts of solvent (ethyl acetate) into a reaction kettle, and stirring and refluxing at a temperature of 38° C.; Step S12, stirring the reaction until the viscosity reaches 280 mPa·s, slowly dripping 10 parts of multifunctional acrylate (ethoxylated trimethylolpropane triacrylate), controlling the dripping rate to 0.07 g / min, dripping until the viscosity reaches 1200 mPa·s, and the dripping of the multifunctional acrylate is completed, the reaction is completed, and cooling is performed to obtain a polyurethane acrylate polymer F. The molecular weight of the polyurethane acrylate polymer F is 970,000 Daltons and the solid content is 49%.
[0048] The preparation of polyurethane acrylate polymer G comprises the following steps: Step S11, adding 45 parts of butyl acrylate, 5 parts of hydroxyethyl acrylate, 1 part of isocyanate (octadecyl isocyanate), 1 part of initiator (tert-butyl peroxyhexahydroterephthalate), and 100 parts of solvent (a mixed solvent of 80 parts of ethyl acetate and 20 parts of toluene) into a reaction kettle, and stirring and refluxing at a temperature of 35° C.; Step S12, stirring the reaction until the viscosity reaches 230 mPa·s, slowly adding 12 parts of multifunctional acrylate (pentaerythritol triacrylate), controlling the dropping rate to 0.08 g / min, and adding until the viscosity reaches 1300 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining polyurethane acrylate polymer G, gelation occurs, the molecular weight of polyurethane acrylate polymer G is 1.05 million Daltons, and the solid content is 51%.
[0049] The preparation of polyurethane acrylate polymer H comprises the following steps: Step S11, adding 40 parts of butyl acrylate, 45 parts of hydroxyethyl acrylate, 20 parts of isocyanate (isophorone diisocyanate), 5 parts of initiator (azobisisoheptanenitrile), and 100 parts of solvent (ethyl acetate) into a reaction kettle, and stirring and refluxing at a temperature of 38° C.; Step S12, stirring the reaction until the viscosity reaches 280 mPa·s, slowly adding 10 parts of multifunctional acrylate (ethoxylated trimethylolpropane triacrylate), controlling the dropping rate to 0.07 g / min, and adding until the viscosity reaches 1400 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining polyurethane acrylate polymer H, the molecular weight of polyurethane acrylate polymer H is 1.08 million Daltons, the solid content is 53%, and severe gelation occurs in the polymer.
[0050] The preparation of polyurethane acrylate polymer I comprises the following steps: Step S11, adding 40 parts of butyl acrylate, 45 parts of hydroxyethyl acrylate, 20 parts of isocyanate (isophorone diisocyanate), 5 parts of initiator (azobisisoheptanenitrile), and 100 parts of solvent (ethyl acetate) into a reaction kettle, and stirring and refluxing at a temperature of 38° C.; Step S12, stirring the reaction until the viscosity reaches 280 mPa·s, slowly adding 2 parts of multifunctional acrylate (ethoxylated trimethylolpropane triacrylate), controlling the dropping rate to 0.07 g / min, and adding until the viscosity reaches 300 mPa·s, and the multifunctional acrylate is added and the reaction is completed, cooling, and obtaining polyurethane acrylate polymer I, the molecular weight of polyurethane acrylate polymer I is 200,000 Daltons, and the solid content is 22%.
[0051] Example 1
[0052] The raw materials of the adhesive layer in this embodiment are composed of the components calculated by weight in the following Table 1: Table 1 Raw material components of the adhesive layer in Example 1
[0053] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 16MPa, and the elongation at break is 450%, baking at 70°C for 10min to obtain a 50μm thick adhesive layer, covering it with a release film, and obtaining an acid and alkali resistant UV anti-viscosity tape.
[0054] Example 2
[0055] The raw materials of the adhesive layer in this embodiment are composed of the components calculated by weight in the following Table 2: Table 2 Raw material components of the adhesive layer in Example 2
[0056] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 18 MPa, and the elongation at break is 500%, baking at 75°C for 10 minutes to obtain a 50 μm thick adhesive layer, covering it with a release film, and obtaining an acid and alkali resistant UV anti-viscosity tape.
[0057] Example 3
[0058] The raw materials of the adhesive layer in this embodiment are composed of the components calculated by weight in Table 3 below: Table 3 Raw material components of the adhesive layer in Example 3
[0059] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 20MPa, and the elongation at break is 550%, baking at 80°C for 8min to obtain a 50μm thick adhesive layer, covering it with a release film, and obtaining an acid and alkali resistant UV anti-viscosity tape.
[0060] Example 4 The raw materials of the adhesive layer in this embodiment are composed of the components calculated by weight in Table 4 below: Table 4 Raw material components of the adhesive layer in Example 4
[0061] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22: coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 22 MPa, The elongation at break is 580%. The adhesive layer with a thickness of 50 μm is obtained by baking at 85° C. for 7 minutes. The release film is then applied to obtain an acid-base resistant UV adhesive tape.
[0062] Example 5 The raw materials of the adhesive layer in this embodiment are composed of the components calculated by weight in Table 5 below: Table 5 Raw material components of the adhesive layer in Example 5
[0063] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 15 MPa, the elongation at break is 400%, baking at 85°C for 7 minutes to obtain a 50 μm thick adhesive layer, covering it with a release film, and obtaining an acid and alkali resistant UV anti-viscosity tape.
[0064] Example 6 The raw materials of the adhesive layer in this embodiment are composed of the components calculated by weight in Table 6 below: Table 6 Raw material components of the adhesive layer in Example 6
[0065] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 30 MPa, and the elongation at break is 800%, baking at 85°C for 7 minutes to obtain a 50 μm thick adhesive layer, covering it with a release film, and obtaining an acid and alkali resistant UV anti-viscosity tape.
[0066] Comparative Example 1 The raw materials of the adhesive layer in this comparative example are composed of the components calculated by weight in the following Table 7: Table 7 Raw material components of the adhesive layer in Comparative Example 1
[0067] Step S2, preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, the tensile strength of the PO film is 22MPa, and the elongation at break is 580%, baking at 85°C for 7min to obtain a 50μm thick adhesive layer, and covering it with a release film to obtain a UV anti-adhesive tape.
[0068] Comparative Example 2 Compared with Example 1, the tensile strength of the PO film used in Comparative Example 2 is 35 MPa, the elongation at break is 200%, and the remaining raw material components and preparation method are consistent with those in Example 1, thereby obtaining a UV anti-viscosity tape.
[0069] Comparative Example 3 Compared with Example 1, the amount of curing agent used in the raw materials of the adhesive layer in Comparative Example 3 is 3 parts by weight, and the remaining raw material components and preparation method are consistent with those in Example 1, thereby obtaining a UV anti-adhesive tape.
[0070] Comparative Example 4 Compared with Example 1, the amount of curing agent used in the raw material of the adhesive layer in Comparative Example 4 is 0.1 parts by weight, and the remaining raw material components and preparation method are consistent with those in Example 1, thereby obtaining a UV anti-adhesive tape.
[0071] Comparative Example 5 Compared with Example 1, the amount of photoinitiator used in the raw materials of the adhesive layer in Comparative Example 5 is 0.05 parts by weight, and the remaining raw material components and preparation method are consistent with those in Example 1, thereby obtaining a UV anti-adhesive tape.
[0072] Comparative Example 6 Compared with Example 1, the raw materials for coating the adhesive layer on the PO film have a tensile strength of 16 MPa and an elongation at break of 450%. The film is baked at 70°C for 10 minutes to obtain a 3 μm thick adhesive layer. The remaining raw material components and preparation method are consistent with those in Example 1, and a UV anti-adhesive tape is obtained.
[0073] Comparative Example 7 Compared with Example 1, the polyurethane acrylate polymer used in Comparative Example 7 is polyurethane acrylate polymer H, and the remaining raw material components and preparation method are consistent with those in Example 1, thereby preparing a UV anti-viscosity tape.
[0074] Comparative Example 8 Compared with Example 1, the polyurethane acrylate polymer used in Comparative Example 8 is polyurethane acrylate polymer I, and the remaining raw material components and preparation method are consistent with those in Example 1, to prepare a UV anti-viscosity tape.
[0075] The following performance tests were performed on Examples 1 to 6 and Comparative Examples 1 to 8: (1) Adhesion performance test The prepared adhesive tape was brought into contact with a glass plate, and a 2kg rubber roller was used to reciprocate once in the length direction of the sample at a speed of 300mm / min, thereby pressing the adhesive tape to obtain an evaluation sample. The sample width was 25mm. The force (peeling force: gf / 25mm) required to peel the adhesive tape in the evaluation sample from the adherend at an angle of 180° was measured according to GB / T2792-1998 (machine pull test), and the average value of the values measured for each evaluation sample was taken as the measured value.
[0076] The same test method as above was used to prepare the evaluation samples of the embodiments and comparative examples. After being irradiated with UV energy, the force required to peel the adhesive tape from the adherend at 180° was measured.
[0077] (2) Residual glue performance test The evaluation samples of the embodiments and comparative examples were prepared by the same method as above. After being irradiated with UV energy, they were peeled off by hand to observe whether there was any residual adhesive on the glass plate.
[0078] (3) Acid resistance test The evaluation samples of the embodiments and comparative examples were prepared by the same method as above. The evaluation samples were sprayed with a mixed solution of HCl and HF, the concentration of HCl was 0.1 mol / L, the concentration of HF was 0.05 mol / L, the spray flow rate was 10 g / min, and after spraying for 5 minutes, the peeling force was tested before UV energy irradiation and after UV energy irradiation after acid solution treatment.
[0079] (4) Alkali resistance test The evaluation samples of each embodiment and comparative example were prepared by the same method as above. The evaluation samples were sprayed with NaOH solution. The concentration of NaOH solution was 0.1 mol / L and the spray flow rate was 10 g / min. After spraying for 5 minutes, the peeling force was tested before UV energy irradiation and after UV energy irradiation after alkaline solution treatment.
[0080] The test results of the bonding performance and residual adhesive performance are shown in Table 8 below, and the test results of the acid resistance test and the alkali resistance test are shown in Table 9 below.
[0081] Table 8 Adhesion performance and residual adhesive performance test results
[0082] Table 9 Acid resistance test and alkali resistance test results
[0083] The samples of acid-base resistant UV adhesive tapes prepared in Examples 1-6 had peeling forces of more than 1800 gf / 25 mm before UV energy irradiation, and had relatively high bonding strength. After irradiation at a relatively low UV energy intensity, the peeling strength of the adhesive layer was significantly reduced, and the adhesive layer had good removability. After acid-base treatment, the bonding force was almost not attenuated, and there was no residual adhesive after peeling.
[0084] In Comparative Example 1, the raw material ratio of the polyurethane acrylate polymer is not within the formula range, the rigid modulus of the obtained colloid is too large, and it cannot have good wetting performance on the material. The initial adhesion is low. After acid / alkali treatment, the adhesion is still large after UV light irradiation, and there is residual glue, which cannot guarantee the protection of the adhered object.
[0085] In Comparative Example 2, the tensile strength of the PO film is too large and the elongation at break is too small. Although the viscosity-reducing tape without acid-base treatment has good initial adhesion, the adhesion is greatly attenuated after acid-base treatment, and there is residual adhesive. This is because the selected PO film is too rigid, and it is impossible to ensure that the edge of the PO film can be well attached to the object being adhered, resulting in acid and alkali penetration from the side.
[0086] In Comparative Example 3, excessive curing agent was added to the raw materials of the adhesive layer, resulting in poor wettability of the obtained adhesive layer, resulting in low initial bonding force. In Comparative Example 4, the amount of curing agent in the raw materials of the adhesive layer was too little, resulting in insufficient resin curing degree of the adhesive layer, resulting in insufficient colloid cohesion, soft colloid, high wettability to the adhered object, resulting in high initial bonding force, but residual adhesive after UV. In Comparative Example 5, the amount of photoinitiator added to the raw materials of the adhesive layer was too little, and the obtained tape had poor viscosity reduction effect after UV.
[0087] In Comparative Example 6, the thickness of the adhesive layer is too small, and the initial bonding force is low. In Comparative Example 7, a polyurethane acrylate polymer with too high a molecular weight and solid content is used, which causes the polymer to gel, and the initial bonding force of the sample is low. In Comparative Example 8, a polyurethane acrylate polymer with too low a molecular weight and solid content is used, and a high initial bonding force cannot be formed due to the low molecular weight.
[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An acid and alkali resistant UV adhesive tape, characterized in that: It includes a PO film layer, an adhesive layer and a release film layer arranged in sequence from top to bottom; Calculated by weight, the raw materials of the adhesive layer include the following components: 100 parts of polyurethane acrylate polymer, 0.1 to 1 parts of photoinitiator and 0.2 to 2 parts of curing agent; The raw materials of the polyurethane acrylate polymer include the following components calculated by weight: 5 to 40 parts of butyl acrylate, 10 to 45 parts of hydroxyethyl acrylate, 2 to 20 parts of isocyanate, 1 to 10 parts of multifunctional acrylate, 0.1 to 5 parts of initiator and 100 parts of solvent; The multifunctional acrylate is selected from any one or more combinations of trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate; The material of the PO film layer is a PO film, the tensile strength of the PO film is 15-30 MPa, and the elongation at break is 400%-800%; The thickness of the adhesive layer is 5 to 200 μm; The molecular weight of the polyurethane acrylate polymer is 300,000 to 1,000,000 Daltons, and the solid content is 30 to 50%.
2. The acid and alkali resistant UV adhesive tape according to claim 1, characterized in that: The isocyanate is selected from any one or more combinations of 4-phenylbenzyl isocyanate, isophorone diisocyanate, 3-ethylphenyl isocyanate, octadecyl isocyanate, p-toluene isocyanate and triphenylmethane triisocyanate.
3. The acid and alkali resistant UV adhesive tape according to claim 1, characterized in that: In the raw materials of the polyurethane acrylate polymer, the initiator is selected from any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, benzoyl peroxide, tert-butyl peroxyhexahydroterephthalate and tert-butyl peroxy-2-ethylhexylate.
4. The acid and alkali resistant UV adhesive tape according to claim 1, characterized in that: The solvent is selected from any one or more combinations of toluene, ethyl acetate, butyl acetate and butanone.
5. The acid and alkali resistant UV adhesive tape according to claim 1, characterized in that: Among the raw materials of the bonding layer, the photoinitiator is selected from any one or more combinations of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-methylphenylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, benzoin dimethyl ether, xylene ketone, 2-isopropylthioxanthone and 2,4,6-(trimethylbenzoyl)-diphenylphosphine oxide.
6. The acid and alkali resistant UV adhesive tape according to claim 1, characterized in that: The curing agent is selected from any one or more combinations of Bayer L75 curing agent, Bayer N3300 curing agent, Bayer 3175 curing agent and Covestro N75 curing agent.
7. A method for preparing an acid-base resistant UV adhesive tape, characterized in that: The method for preparing the acid-base resistant UV adhesive tape according to any one of claims 1 to 6 comprises the following steps: Step S1, preparing polyurethane acrylate polymer: Step S11, stirring and refluxing the formulated amounts of butyl acrylate, hydroxyethyl acrylate, isocyanate, initiator and solvent at a temperature of 35-45° C.; Step S12, stirring and reacting until the viscosity reaches 200-300 mPa·s, slowly adding multifunctional acrylate at a dropping rate of 0.01 g / min-0.1 g / min, and cooling after the multifunctional acrylate is added and the reaction is completed, to obtain a polyurethane acrylate polymer; Step S2: Preparation of acid and alkali resistant UV adhesive tape: Step S21, uniformly mixing the polyurethane acrylate polymer, the photoinitiator and the curing agent in the formula amount to obtain the raw material of the adhesive layer; Step S22, coating the raw material of the adhesive layer on the PO film, baking at a temperature of 60-100° C. for 5-10 minutes to obtain the adhesive layer, covering it with a release film, and obtaining an acid-base resistant UV anti-viscosity tape.
8. Use of the acid-base resistant UV anti-adhesive tape according to any one of claims 1 to 6 in the fields of wafer cutting, semiconductors, glass thinning and 3C electronic materials.
Citation Information
Patent Citations
Hydroxyl-containing viscosity-reducing glue composition as well as preparation method and application thereof
CN114015388A
Ultraviolet debonding protective film for wafer cutting as well as preparation method and application of ultraviolet debonding protective film
CN117186790A
Cited By
Acid and alkali resistant UV visbreaking adhesive, visbreaking adhesive film and visbreaking adhesive tape
CN121427450A